2015
DOI: 10.1093/jxb/erv173
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the cis elements in the proximal promoter regions of the anthocyanin pathway genes reveals a common regulatory logic that governs pathway regulation

Abstract: HighlightMYB and bHLH bind to two identifiable syntaxes present in target gene promoters, and the anthocyanin pathway is regulated as one unit as in other branches of the flavonoid network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 76 publications
5
77
0
Order By: Relevance
“…Promoter regions were analysed using the SoftBerry suite (http://www.softberry.com/) and screened for cis ‐acting elements using the New PLACE database (http://www.dna.affrc.go.jp/htdocs/PLACE/; Higo et al ., ). Specific binding sites corresponding to consensus sequences for MYB (ANCNNCC), bHLH (CACNH(G/T)) recognition elements (Wang et al ., ; Zhu et al ., ), and WRKY ((T)(T)TGACY) recognition elements (W‐boxes, Eulgem et al ., ; Pesch et al ., ) were found and then localized using PlantPAN 2.0 database (http://plantpan2.itps.ncku.edu.tw/; Chow et al ., ; Figure S5).…”
Section: Methodsmentioning
confidence: 99%
“…Promoter regions were analysed using the SoftBerry suite (http://www.softberry.com/) and screened for cis ‐acting elements using the New PLACE database (http://www.dna.affrc.go.jp/htdocs/PLACE/; Higo et al ., ). Specific binding sites corresponding to consensus sequences for MYB (ANCNNCC), bHLH (CACNH(G/T)) recognition elements (Wang et al ., ; Zhu et al ., ), and WRKY ((T)(T)TGACY) recognition elements (W‐boxes, Eulgem et al ., ; Pesch et al ., ) were found and then localized using PlantPAN 2.0 database (http://plantpan2.itps.ncku.edu.tw/; Chow et al ., ; Figure S5).…”
Section: Methodsmentioning
confidence: 99%
“…UGT75C1 is also upregulated by PAP1, encoding an MYB transcription factor [47]. As a whole, the TF complex (TT2, TT8, and TTG1) and SmMYB1, an R2R3 MYB transcription factor, can regulate all anthocyanin pathway genes [73,75]. In this study, we identified thousands of TFs, including TFs for TAC synthesis, which might be involved in the regulation of genes in the TAC metabolic pathway.…”
Section: Discussionmentioning
confidence: 98%
“…The TFs include MYB, bHLH, and WDR. In Arabidopsis thaliana, the PAP1-GL3-TTG1 complex can regulate the TFs of MYB and bHLH [73]. In addition, the reduction of MYB expression can reduce the expression levels of DFR, LDOX, GST12, F3'H and UGT75C1 in the TAC pathway [74].…”
Section: Discussionmentioning
confidence: 99%
“…The same candidate regions appear in the results of different ΔSNP-indexes, and the intersection of these regions was selected as the final candidate region. In the genomic candidate region, it is preferred to use the rice genome annotation site MSU-RGAP (http://rice.plantbiology.msu.edu/) to annotate the genes in the candidate region, and the genes related to plant anthocyanin synthesis (Zhu et al, 2015); secondly, the candidate region containing candidate gene or adjacent to the known gene related to anthocyanin synthesis in rice were taken as a candidate gene; finally, the homozygous variation site with a sequencing depth of not less than 4× and ΔSNP-index=1 was selected as a candidate gene. At the same time, by referring to the method of Yano et al(Yano et al, 2016), all the polymorphisms in the candidate region were classified into three types.…”
Section: Construction Of Genomic Dna Poolsmentioning
confidence: 99%